The Effect of Green Accounting Disclosure on Firm Value with Financial Performance as a Moderating Variable - Nur Indah Kusuma Ningrum; Iis Ismawati (Pascasarjana Universitas Sultan Ageng Tirtayas, 2026)
This study aims to examine the effect of green accounting disclosure on firm value with financial performance as a moderating variable. The study population consists of companies in the energy and primary consumer goods sectors listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The method used was purposive sampling with a sample size of 74 data points obtained from annual reports and sustainability reports accessed via the official IDX website and company websites. Data processing was carried out using SPSS version 27 software with multiple linear regression analysis and moderated regression analysis (MRA). The results of the study indicate that green accounting disclosures have a positive and significant effect on firm value, whilst financial performance weakens the effect of green accounting disclosures on firm value.